2013
DOI: 10.1164/rccm.201212-2227oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Responsive Innate Lymphoid Cells Are an Important Source of IL-13 in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Rationale: Chronic rhinosinusitis (CRS) without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP) are associated with Th1 and Th2 cytokine polarization, respectively; however, the pathophysiology of CRS remains unclear. The importance of innate lymphoid cells in Th2-mediated inflammatory disease has not been clearly defined. Objectives: The objective of this study was to investigate the role of the epithelial cell-derived cytokine IL-33 and IL-33-responsive innate lymphoid cells in the pathophysiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
224
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(244 citation statements)
references
References 33 publications
17
224
2
1
Order By: Relevance
“…This study also showed that the ILC2s from CRS patients responded to IL-33-mediated stimulation by producing IL-13 (Shaw et al 2013), further suggesting that ILC2s may contribute to the pathogenesis of allergic upper airway disease in humans. Consistent with previous findings (Mjosberg et al 2012), TSLP has recently been shown to be highly expressed in the nasal polyps of CRS patients (Nagarkar et al 2013).…”
Section: Group 2 Innate Lymphoid Cellssupporting
confidence: 56%
See 2 more Smart Citations
“…This study also showed that the ILC2s from CRS patients responded to IL-33-mediated stimulation by producing IL-13 (Shaw et al 2013), further suggesting that ILC2s may contribute to the pathogenesis of allergic upper airway disease in humans. Consistent with previous findings (Mjosberg et al 2012), TSLP has recently been shown to be highly expressed in the nasal polyps of CRS patients (Nagarkar et al 2013).…”
Section: Group 2 Innate Lymphoid Cellssupporting
confidence: 56%
“…Multiple reports indicate that IL-33 is a potent activator of IL-13-producing ILC2s in allergic airway inflammation (Bartemes et al 2012;Beamer et al 2012;Mjosberg et al 2012;Salmond et al 2012;Hung et al 2013;Shaw et al 2013), but other epithelial cell-derived cytokines, bioactive lipids, and inflammatory factors also contribute to the development of pathogenic ILC2 responses in the lung. A recent study has shown that TSLP can contribute to ILC2 activation that promotes corticosteroid resistance in the context of IL-33-mediated airway inflammation (Kabata et al 2013).…”
Section: Ilc2s and Allergic Airway Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…ILC22 cells secreting IL-22 in lungs exert an antiinflammatory effect during experimental allergic asthma and inhibit acute hypersensitivity reaction (AHR) and pulmonary inflammation. Besides in asthma, group 2 ILCs also play a significant role in the pathogenesis of chronic rhinosinusitis (CRS) by releasing IL-13 in response to IL-33 released through nasal epithelial cells (18). CRS is a chronic inflammatory condition of the nasal and paranasal sinus mucosa affecting more than 30 million people annually (18).…”
Section: Ilcs In Chronic Respiratory Tract Inflammatory Disorders (Imentioning
confidence: 99%
“…Past studies established that ILC2 cells were increased in subjects with asthma and nasal polyposis, compared with subjects without allergic inflammation (38). Shaw and colleagues showed that subjects with chronic rhinosinusitis and nasal polyposis had a higher percentage of ILC2 cells compared with subjects with chronic rhinosinusitis alone, and these cells had the capacity to produce IL-13 in response to IL-33 (39). Thus, ILC2 cells from human nasal polyps have the functional capacity to drive allergy and asthma.…”
Section: Biological Pathways That Influence Diseasementioning
confidence: 99%